INTERPRETATION OF THE IMAGE OF MASHRAB IN MIRKARIM ASIM'S STORY "SINGAN SETOR" - Sultonova, Vazira (FILOLOGIYA UFQLARI JURNALI, 2024)
This article discusses the analysis of the image of Mashrab in Mirkarim Asim's short story "Singan Setor". This short story is analyzed in comparison with "Qissai Mashrab" from folk books. The article draws relevant conclusions on the interpretation of the image of Mashrab in both works.